LMX and employee satisfaction: mediating effect of psychological capital. Issue 3 (2nd May 2017) - Liao, Shu-sien; Hu, Da-chian; Chung, Yu-Chun; Chen, Li-Wen
Abstract : Purpose: The purpose of this paper is to investigate the relationship between leader-member exchange (LMX), job satisfaction (JS), life satisfaction (LS), and psychological capital (PC) for employee relation management. Design/methodology/approach: A total of 319 valid questionnaires were received from employees of financial and electronics manufacturing industries in Taiwan, and they were then analyzed using a structuring equation model with SPSS 12.0 and LISREL 8.8. Findings: Good LMX increases psychological capital. Psychological capital enhances both JS and LS, and psychological capital serves as a full mediator for both JS and LS. A moderating effect of industrial characteristics is found between LMX and LS and between psychological capital and LS. Practical implications: The findings suggest that managers need to focus on leadership style in order to develop employees' life and JS through building psychological capital. Originality/value: This study not only obtained further support for predictions derived from the LMX theory but was also a more extensive analysis of the meaningful relationships between job and LS with a mediating effect of psychological capital on employee relation management.